The Politics of Energy Conservation - Nivola, Pietro S.; Brookings Institution (Washington, D.C.: Brookings Institution, 1986)
In this book, the author examines key legislative decisions of the 1970s and early 1980s on the pricing of crude oil and natural gas, as well as decisions on fuel taxes and electric rates.. He further explores the influence of interest groups, popular attitudes, and regional rivalries that often delayed or complicated energy-saving price reforms. He also analyzes the roles of government leaders and political institutions in shaping policy.
Includes index.
Includes bibliographical references
ne 18/04/2018
Loans
Keywords: Energy Conservation; Energy Policy